2014
DOI: 10.1155/2014/131920
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Awareness among Medical Students and Their Vaccination Status at Syrian Private University

Abstract: Background. Hepatitis B virus (HBV) is a potentially life-threating infection and a well-recognized occupational hazard for healthcare workers including medical students. Methods. A cross-sectional study was conducted at Syrian Private University (SPU), Faculty of Medicine, to assess the knowledge and awareness about hepatitis B, the status of hepatitis B vaccination, and the reasons for not getting vaccinated among the first-and the fifth-year medical students. Results. The present study demonstrates surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
90
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(106 citation statements)
references
References 27 publications
11
90
4
1
Order By: Relevance
“…transfusion of blood, sexual intercourse, mother to her baby respectively. 14 The preventive measures were better known to our students compared to Study in Jammu where they reported that use of condoms and sterile needles was proposed by 20%, avoidance of addiction by 50%, and immunization with hepatitis vaccine by 60% of the women as preventive measures against HBV infection.…”
Section: Discussionmentioning
confidence: 85%
“…transfusion of blood, sexual intercourse, mother to her baby respectively. 14 The preventive measures were better known to our students compared to Study in Jammu where they reported that use of condoms and sterile needles was proposed by 20%, avoidance of addiction by 50%, and immunization with hepatitis vaccine by 60% of the women as preventive measures against HBV infection.…”
Section: Discussionmentioning
confidence: 85%
“…General excuses for not having their HBV status tested, was lack of motivation(36.76%), lack of time to check (21.54%), no family history of hepatitis(13.87%), fear of injection(10.76%), they were not familiar with HBV screening (7.51%) and from where to have the test done (9.31%). A study conducted in Syria also revealed that the main reason for not being vaccinated is the lack of motivation (34.2%) 8 . In one study it was explored that majority of the participants knew that hepatitis B can be transmitted during childbirth (83%) and by anybody who looks and feels well (78%) 26 .…”
Section: Respondents' Knowledge About Treatment and Vaccinationmentioning
confidence: 99%
“…The quantifiable symptoms and usual history of HBV infection differ with age. Clinical acute hepatitis B is usually more common in adults than children, and the possibility of becoming a chronic carrier of hepatitis B is larger in children than adults: 80-90% of populace perinatally infected compared to <5% of infections going on in adults 8 . HBV infection is primarily acquired during birth and infancy, and vertical communication accounts for more than 50% of the chronic infection cases 4,5,13,29,31 .…”
mentioning
confidence: 99%
See 2 more Smart Citations